If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6v+16=-2(v-6)
We move all terms to the left:
-6v+16-(-2(v-6))=0
We calculate terms in parentheses: -(-2(v-6)), so:We get rid of parentheses
-2(v-6)
We multiply parentheses
-2v+12
Back to the equation:
-(-2v+12)
-6v+2v-12+16=0
We add all the numbers together, and all the variables
-4v+4=0
We move all terms containing v to the left, all other terms to the right
-4v=-4
v=-4/-4
v=1
| 216=1/3(36)h | | 7+6*x=4^2+x^2 | | 6x-(-4(x+1))=2x+4 | | x/12+5/9=11/36 | | 8=-18+3/8(16-40m) | | 14(z-3)=2-3z | | -17x-1-10x+17=32x+1 | | 15x-15-7x+63=4x | | -4(n+1)+15n=0 | | 40/24=20/a | | x2+-121x+5=0 | | -3(4r-8)=36-12r | | 6x(-4(x+1))=2x+4 | | −2w=−9 | | 5x+4=99 | | -10+3n=2 | | (17+2x)+23=180 | | n/4-2+4=12 | | 5x−2(x+1)=14 | | -13.92=4+w/7 | | 4-14x=-8+15x | | 3(9-6x)=63 | | 13k+15=54 | | 2k-3(2k-3)=4.5 | | 8x-5=5x+15 | | 2/1(2x-10)=4 | | 8(1+8r)=-8r+8 | | 3/4x-6=-15 | | (m-8)2=0 | | -5/4(9+2x)=40 | | 43v-32=97 | | 7/12x=5/6x-5 |